Linking Human Development and the Financial Responsibility of Regions: Combined Index Proposals Using Methods from Data Envelopment Analysis - Ferraz, Diogo; Mariano, Enzo B. [UNESP]; Rebelatto, Daisy; Hartmann, Dominik (Springer, 2020)
Several indicators on human development and capabilities have been introduced in recent decades that measure the absolute level of deprivations and freedoms of people. However, these indicators typically do not consider to what extent regions and countries efficiently spend their limited financial resources on improving human development. This is an important shortcoming because regions typically face different financial constraints in developing social policies and promoting human development. In this article, we advance methods from data envelopment analysis (DEA) to measure absolute capability values and the social efficiency of 129 Brazilian mesoregions. We present a new indicator called the Capability Index Adjusted by Social Efficiency (CIASE) that evaluates the human development performance of regions based on their absolute levels of deprivations as well as their social efficiency in translating limited financial resources into human development. Moreover, we introduce a Deprivation and Financial Responsibility based Prioritization Index (DFRP) that helps to identify priority regions for higher public expenditures in human development. Our results for the case of Brazil show that several poor regions perform relatively better in terms of social efficiency than in terms of absolute human development. Conversely, several rich regions perform relatively worse in terms of social efficiency than in absolute values. Thus, our analysis shows how DEA methods can help to bridge perspectives that are often presented as separated issues but could be strong allies for development: attending to human deprivation and promoting social efficiency.
Keywords: Human development; Data envelopment analysis (DEA); Social efficiency; Financial responsibility; Brazilian mesoregions